Educação especial e educação de jovens e adultos: os desdobramentos na interconexão em uma turma da EJA da rede estadual em Belém/Pa - ARAÚJO, Danielle Sena de (2020)
The present work presents developments in the interconnection between Youth and Adult Education and Inclusive Education based on the reality of a class in a state school in the city of Belém / PA. This is a qualitative research, of the type of case study, which was motivated by the question: how are the developments in the interconnection of Inclusive Education and Education of Youth and Adults? It aims to analyze aspects that can configure these unfolding, and as an investigative instrument, on-site observations were used, and a questionnaire was applied to the class teacher, and interpretive analysis was used as the method of analysis. The results indicated that although the teacher in her answers sometimes made a mistake in the inclusive discourse, she was able to talk for a few moments with the ESA teacher, so that the practices would approach as much as possible for an education for all, for a citizen education. We believe in the possibility of an articulation between the institutional organizations and of educational practices that allow the disabled student in an EJA class to broaden their view on the knowledge acquired throughout the life, for that, it becomes necessary that the theory and the doing inclusive education are more perennial for the development of this proposal.